2023
DOI: 10.7554/elife.80360
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequence to structure analysis from comprehensive pairwise mutagenesis of multiple self-cleaving ribozymes

Abstract: Self-cleaving ribozymes are RNA molecules that catalyze the cleavage of their own phosphodiester backbones. These ribozymes are found in all domains of life and are also a tool for biotechnical and synthetic biology applications. Self-cleaving ribozymes are also an important model of sequence to function relationships for RNA because their small size simplifies synthesis of genetic variants and self-cleaving activity is an accessible readout of the functional consequence of the mutation. Here we used a high-th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
6
13
0
Order By: Relevance
“…Two pK a values were inferred for each construct: pK a1 ≈ 9.0 probably corresponding to a hydrated Mg 2+ ion and pK a2 ≈ 6.0 related to the catalytic cytosine residue (table S3). Furthermore, we confirmed the inactivation of all tRNA/Θrz pairs upon mutating the catalytic cytosine to uracil (CΔU), in line with known HDV-like behavior (29). This observation further validates our approach for identifying false-positives in the bioinformatic search (Fig.…”
Section: Trna-associated θRzs Are Active In Vitrosupporting
confidence: 83%
See 1 more Smart Citation
“…Two pK a values were inferred for each construct: pK a1 ≈ 9.0 probably corresponding to a hydrated Mg 2+ ion and pK a2 ≈ 6.0 related to the catalytic cytosine residue (table S3). Furthermore, we confirmed the inactivation of all tRNA/Θrz pairs upon mutating the catalytic cytosine to uracil (CΔU), in line with known HDV-like behavior (29). This observation further validates our approach for identifying false-positives in the bioinformatic search (Fig.…”
Section: Trna-associated θRzs Are Active In Vitrosupporting
confidence: 83%
“…We chose eight recently annotated viral databases from diverse environments (table S1) and cross-referenced all subsequent hits with tRNA motif searches in the same databases. To increase motif specificity, we incorporated false-positive motifs as internal controls, considering previous findings that drzs are inactivated by a cytosine-to-uracil mutation (CΔU) at the active site (28), with no observed rescue mutation at this position (29). Each search was conducted with four different descriptor files, one active ribozyme motif with the catalytic cytosine residue intact (first position in the J4/2 junction) and three false-positive motifs containing substitutions at this residue (CΔA, CΔG, and CΔU, respectively; Fig.…”
Section: Identification Of Trna-associated θRzs In Bacteriophagesmentioning
confidence: 99%
“…We chose eight recently annotated viral databases 23 , 29 35 from diverse environments (Supplementary Table 1 ) and cross-referenced all subsequent hits with tRNA motif searches in the same databases. To increase motif specificity, we incorporated false-positive motifs as internal controls, considering previous findings that drzs are inactivated by a cytosine-to-uracil mutation (CΔU) in the active site 36 , with no observed rescue mutation at this position 37 . Each search was conducted with four different descriptor files, one active ribozyme motif with the catalytic cytosine residue intact (first position in the J4/2 junction) and three false-positive motifs containing substitutions at this residue (CΔA, CΔG, and CΔU, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10,[13][14][15]17,18 Mutational studies have demonstrated that changes to the general acid and general base are not well-tolerated. [12][13][14]17,19 The reaction can also be assisted by buffer catalysis under biological reaction conditions. 20 Additionally, ∼90% of the twister ribozymes that were initially predicted by Breaker and co-workers possess one or more auxiliary stem-loops, referred to as P3 and P5 (Figure 1A).…”
mentioning
confidence: 99%
“…Twister ribozymes have been studied extensively, and many of their structural and biochemical properties have been elucidated. , Structurally, the catalytic core of the twister ribozyme is comprised of three essential pairings, P1, P2, and P4 (Figure A), although variants suggest that P1 is dispensable for self-cleavage. , The cleavage site is located between residues −1 and 1 in L1, where residue −1 can be any nucleotide and residue 1 is a conserved A . Self-cleavage occurs via a general acid–base mediated mechanism, in which A1 acts as the general acid and the first G on the 3′ strand of L1 acts as the general base. , ,, Mutational studies have demonstrated that changes to the general acid and general base are not well-tolerated. ,, The reaction can also be assisted by buffer catalysis under biological reaction conditions . Additionally, ∼90% of the twister ribozymes that were initially predicted by Breaker and co-workers possess one or more auxiliary stem-loops, referred to as P3 and P5 (Figure A) .…”
mentioning
confidence: 99%